Trends and associated characteristics for Chagas disease among women of reproductive age in the United States, 2002 to 2017. (November 2020) - Ikedionwu, Chioma; Dongarwar, Deepa; Kaur, Manvir; Nunez, Lisa; Awazi, Annabella; Mallet, Jere'; Kennedy, KaShena; Cano, Michelle; Dike, Chinwe; Okwudi, Jessica; Stewart, Justice; Igwegbe, David; et al.
Abstract: Background: American trypanosomiasis, commonly referred to as Chagas disease, is caused by a single cell protozoan known as Trypanosoma cruzi ( T. cruzi ). Although those affected are mainly in Latin America, Chagas has been detected in the United States (US), Canada and in many European countries due to migration. Few studies have explored the epidemiology of Chagas within the US or changes in disease burden over the past decade. The objective of this study was to explore the trends and associated characteristics for Chagas disease among hospitalized women of reproductive age in the US. Methods: We analyzed admissions data including socio-demographic and hospital characteristics for inpatient hospitalization for women of reproductive age (15–49 years) in the US from 2002 through 2017. We employed Joinpoint regression analysis to determine trends in the prevalence of Chagas disease over this period. Results: A total of 487 hospitalizations of Chagas disease were identified, corresponding to 3.7 per million hospitalizations over the study period. The rate statistically increased from 1.6 per million in 2002 to 7.6 per million hospitalizations in 2017. Chagas was most prevalent among older women, Hispanics and those in the highest zip income bracket. The in-hospital mortality rate was about 10 times greater among women with Chagas compared to those without the condition (3.1% versus 0.3%), and the condition tended to be clustered in women treated at large, urban teaching hospitals in the Northeastern region of the US. Conclusion: Chagas disease diagnosis appears to be increasing among hospitalized women of reproductive age in the US with a 10-fold elevated risk of mortality. Highlights: 3.7 per million hospitalizations were identified in the US over 2002‐–2017 among women of reproductive age. Chagas was found to be most prevalent among older women, Hispanics and those in the highest zip income bracket. The in-hospital mortality rate was about 10 times greater among women with Chagas compared to those without the condition. Rates of Chagas hospitalizations were found to be increasing at 6.8% annually over the study period.